Biomechanical insights into the dentition of megatooth sharks (Lamniformes: Otodontidae) - Ballell, Antonio (Sci Rep, 2021)
The evolution of gigantism in extinct otodontid sharks was paralleled by a series of drastic modifications in their dentition including widening of the crowns, loss of lateral cusplets, and acquisition of serrated cutting edges. These traits have generally been interpreted as key functional features that enabled the transition from piscivory to more energetic diets based on marine mammals, ultimately leading to the evolution of titanic body sizes in the most recent forms (including the emblematic Otodus megalodon). To investigate this hypothesis, we evaluate the biomechanics of the anterior, lateral, and posterior teeth of five otodontid species under different loading conditions by using two-dimensional finite element analysis. Stress distribution patterns are remarkably similar among all models under puncture and draw (i.e., when subjected to vertical and lateral forces, respectively). Contrary to expectation, higher average stress values are detected under both loading scenarios in more recent species. Altogether, this suggests little correlation between tooth morphology and key aspects of biomechanical behaviour in otodontids, making it difficult to frame the morphological trend of their dentitions within an adaptive scenario. We propose that this pattern most likely emerged as a non-functional by-product of heterochronic processes driven by selection towards larger body sizes.